The importance of transdisciplinary treatment for non-carious cervical lesions and dental hypersensitivity and the influence on quality of life: case report (Research, Society and Development, 2021)
When there is a human pathology, health professionals should not treat patients by specialty. They must treat patients analyzing all areas and pathologies they may have in a transdisciplinary way, restoring the individual's physical, psychological and social well-being. The dental hypersensitivity and non-carious cervical lesions are pathologies that currently have a great worldwide prevalence in dentistry, which influence the patient's quality of life. These pathologies have a multifactorial etiology, and an analysis is important. This article aims to report the clinical case of a patient who presented pain sensitivity grade 9 on the VAS pain scale, which directly influenced her quality of life. The treatment was based on transdisciplinary treatment, involving several specialties of dentistry to solve the treatment. The result was achieved, the patient reported a change to grade 0 on the VAS scale and can return the patient to a better quality of life.